ALACRANITE, AS8S9: STRUCTURAL STUDY OF THE HOLOTYPE AND RE-ASSIGNMENT OF THE ORIGINAL CHEMICAL FORMULA - Bonazzi P.; Bindi L.; Pratesi G.; Menchetti S.; Popova V. (My University, 2003)
Alacranite from the type locality (Uzon caldera, Kamchatka, Russian Federation) was submitted for structural analysis. A single crystal was selected and the following lattice parameters were determined: a = 9.942(4), b = 9.601(2), c = 9.178(3) Å, β = 101.94(3)°, V = 857.1 (5) Å3. The crystal structure was solved in the P2/c space group using direct methods and refined to R = 6.79% for 472 observed reflections. The structure of alacranite consists of an ordered sequence of As4S4 and As4S5 cage-like molecules, with a molecular packing closely resembling that found in the β-As4S4 phase. Both As-As and As-S intramolecular distances are in the range usually observed for covalent bonds. The structural model confirms the chemical formula As8S9 for alacranite, and accounts for differences in the unit-cell parameters of alacranite compared to those of the natural analogue of β-As4S4. This latter mineral, therefore, should receive a new name.
Keywords: Alacranite; Uzon caldera; Kamchatka